Is the Coleman–de Luccia Action Minimum?: An AdS/CFT Approach - Oshita, Naritaka; Shoji, Yutaro; Yamaguchi, Masahide (Progress of Theoretical and Experimental Physics, 2024)
We use the anti-de Sitter/conformal field theory (AdS/CFT) correspondence to find the least bounce action in an AdS false vacuum state, i.e. the most probable decay process of the metastable AdS vacuum within the Euclidean formalism by Callan and Coleman. It was shown that the O(4) symmetric bounce solution leads to the action minimum in the absence of gravity, but it is nontrivial in the presence of gravity. The AdS/CFT duality is used to evade the difficulties particular to a metastable gravitational system. To this end, we show that the Fubini bounce solution in CFT, corresponding to the Coleman–de Luccia (CdL) bounce in AdS, gives the least action among all finite bounce solutions in a conformal scalar field theory. Thus, we prove that the CdL action is the least action among all possible large and thin-wall configurations under certain conditions.